2020
DOI: 10.1590/1678-5150-pvb-6678
|View full text |Cite
|
Sign up to set email alerts
|

Black queen cell virus and Nosema ceranae coinfection in Africanized honey bees from southern Brazil

Abstract: Bees are fundamental in several aspects, especially in relation to plant biodiversity and pollination. Recently, immense losses are being faced in the number of Brazilian colonies, mainly in southern states of the country, which has a strong beekeeping activity. There are indications that, among the reasons for the losses, pathogens that affect the health of bees may be involved. Among them, the microsporidium Nosema and the black queen cell virus (BQCV) stand out for their prevalence. In this study, 92 coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…In both groups, the percentage of infected bees was below 50%. A similar percentage of infected bees (<60%) was also reported in workers of AHB colonies from Brazil [72]. However, other studies have reported infectivity rates of 100% in EHBs inoculated with similar or lower concentration of Nosema spores than the one used in this study [49,73].…”
Section: Discussionsupporting
confidence: 86%
“…In both groups, the percentage of infected bees was below 50%. A similar percentage of infected bees (<60%) was also reported in workers of AHB colonies from Brazil [72]. However, other studies have reported infectivity rates of 100% in EHBs inoculated with similar or lower concentration of Nosema spores than the one used in this study [49,73].…”
Section: Discussionsupporting
confidence: 86%
“…The BQCV infection mainly affects queen larvae and pupae instead and has the highest incidence in spring and early summer; BQCV infected adult bees normally do not exhibit outward disease symptoms [78]. Moreover, several previous reports linked BQCV disease outbreaks with infection of N. apis [74,78,81] and N. ceranae [25,[82][83][84][85], suggesting that these pathogens can act synergistically. Even if many apiaries analysed in this study showed co-infections of BQCV with N. ceranae, no statistically significant association was found, since BQCV infection was always present in almost all the hives.…”
Section: Discussionmentioning
confidence: 99%